Faktor Predisposisi Yang Berhubungan Dengan Kepatuhan Masyarakat Mengkonsumsi Obat Filariasis - Hidayah Afnas, Nur; Septiana Arpen, Ratih (Jurnal Medisains Kesehatan, 2022)
Government efforts to eradicate filariasis is with filariasis mass treatment. But there are still many people who do not want to consume filariasis drugs because they do not know about the importance of the drug to prevent the disease filariasis. Jorong Madani in Padang, there are 3 people with filariasis in 2021, although treatment coverage filariasis in 2019 has reached 100%. Thus there are still many people who do not comply filariasis drugs. Interviews with 10 families in Padang Jorong North Manggopoh Madani, obtained information that 6 of them were told not to take medicine filariasis given officers. The aim of research to determine the predisposing factors associated with compliance in taking medication communities filariasis. This type of research is descriptive analytic with cross sectional approach. The population is all the people who are in Jorong Madani Manggopoh Padang Utara subdistrict Lubuk Basung Agam, totaling 425 people. Samples numbered 64 people taken by simple random sampling. Data were collected through interviews guided, then processed and analyzed by computerized. Results of univariate analysis note that 64.1% of respondents have a low knowledge, 62.5% negative attitude, 68.8% trust unfavorable and 68.6% do not obey the filariasis drug consumption. Bivariate analysis known predisposing factors associated with compliance in drug consumption filariasis is knowledge (p = 0.003 and OR = 6.314), attitude (p = 0.026 and OR = 4.000) and confidence (p = 0.002 and OR = 6.750). It can be concluded that the factors associated with adherence filariasisi drug consumption is the knowledge, attitudes and beliefs. Expected at the health center in order to supervise the community in taking medication filariasis as public advocate to directly take medicine in front of the officer.